Obituary: Irene Whitfield - Kealey, Gregory S.; Cadigan, Sean (Labour / Le Travail, 2013)
Pays homage to Irene Whitfield (1941-2013), who was managing editor of the journal from 1982 to 2007.
Keywords: PERIODICAL editors; WHITFIELD; Irene